Deconstructing agronomic resource use efficiencies to increase food production - Porter, John R.; Thorburn, Peter J.; Brown, Hamish E.; Teixeira, Edmar I.; Moot, Derrick J.; Mills, Annamaria; Christensen, Svend (Italian Journal of Agronomy, 2021)
Food production per unit land area needs to be increased, thus cropping systems need to use nutrients, water and solar radiation at as close to maximal efficiencies as possible. We deconstruct these efficiencies into their components to define a theoretical crop ideosystem, in which all resource use efficiencies are maximised. This defines an upper biological limit to food production. We then quantify the difference between maximum use efficiencies and those observed in three agronomic systems (maize, cocksfoot, sugarcane) and identify how, in actual farm systems, efficiencies can be raised to raise food production. We find that crop nutrient use efficiency can be limited by low water availability; thus adding nutrients would not raise production but adding water would. The converse situation of water use efficiency being affected by nutrition is not as evident. Ideosystem thinking can be used to define small- and large-scale agronomic systems that optimize water and nutrient use to maximise food production. Highlights - Novel ideosystem method of analysing processes of food production, focussing on resource use efficiencies. - Interactions between resource use efficiencies are asymmetrical. - The ideosystem concept portrays how far a production system approaches maximum efficiency.